2018
DOI: 10.14474/ptrs.2018.7.4.179
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vertical ground reaction forces between female elderly and young adults during sit-to-stand and gait using the Nintendo Wii Balance Board

Abstract: Objective: The purpose of this study was to analyze and compare vertical ground reaction forces during sit to stand (STS) and gait between female elderly and young individuals using the Wii Balance Board (WBB). Design: Cross-sectional study. Methods: Fifty-one female elderly people (age: 75.18±4.60 years), and 13 young people (age: 29.85±3.69 years) performed the five times STS test and gait respectively on the WBB. We analyzed time (s), vertical peak (%), integral summation (Int_SUM, %), and counter variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For older adults, the average peak force during swings was almost half that of the Instructor (52.1%), with a mean difference of 4.2 N.kg −1 , highlighting scope for potential improvement from training. Age has previously been shown to have no effect on peak GRF during lifting (Lim et al 2018b; Shin et al 2006), but moderate differences between sex have been observed during Sit-To-Stand tasks in community dwelling older adults (males > females) (Tsuji et al 2015). In the absence of sex-specific health or medical conditions, these results suggest that choice of kettlebell weight should be influenced by bodyweight, strength and/or stature rather than sex.…”
Section: Discussionmentioning
confidence: 97%
“…For older adults, the average peak force during swings was almost half that of the Instructor (52.1%), with a mean difference of 4.2 N.kg −1 , highlighting scope for potential improvement from training. Age has previously been shown to have no effect on peak GRF during lifting (Lim et al 2018b; Shin et al 2006), but moderate differences between sex have been observed during Sit-To-Stand tasks in community dwelling older adults (males > females) (Tsuji et al 2015). In the absence of sex-specific health or medical conditions, these results suggest that choice of kettlebell weight should be influenced by bodyweight, strength and/or stature rather than sex.…”
Section: Discussionmentioning
confidence: 97%